2009
DOI: 10.1111/j.1468-0289.2009.00482.x
|View full text |Cite
|
Sign up to set email alerts
|

Returns on investments during the colonial era: the case of the Belgian Congo1

Abstract: Before the First World War, Belgium participated in a global wave of foreign direct investment. After the war, a shift towards the Belgian colony of the Congo was observed. With regard to these investments, it is commonly argued that higher (expected) profit rates were a strong incentive, although others propose that the colonial powers lost money on their colonial possessions. We measure ex post performance in terms of the time-weighted rate of return by making use of a new database of Congolese stocks and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…As ELEC member Van Esbroek explained in 1951, the open-door policy was the final objective of Europe/Empire co-operation: 'from a merely philosophical point of view, inasmuch as we should aim to complete suppression of tariffs all over the world in a distant future, we might better leave the open-door territories as so many beacons showing the way'. 15 In their analysis of the Brussels and Antwerp stock exchanges, Buelens and Marysse (2009) demonstrated that the free trade system allowed high-performing companies to develop in the Belgian Congo and to finance the necessary trade infrastructures of the colony privately. Unburdened by the expensive public schemes that financed French and British imperial development, neither the Belgian population nor the economic elite could complain about the cost of their empire.…”
Section: The European League For Economic Co-operation: a Transnationmentioning
confidence: 98%
“…As ELEC member Van Esbroek explained in 1951, the open-door policy was the final objective of Europe/Empire co-operation: 'from a merely philosophical point of view, inasmuch as we should aim to complete suppression of tariffs all over the world in a distant future, we might better leave the open-door territories as so many beacons showing the way'. 15 In their analysis of the Brussels and Antwerp stock exchanges, Buelens and Marysse (2009) demonstrated that the free trade system allowed high-performing companies to develop in the Belgian Congo and to finance the necessary trade infrastructures of the colony privately. Unburdened by the expensive public schemes that financed French and British imperial development, neither the Belgian population nor the economic elite could complain about the cost of their empire.…”
Section: The European League For Economic Co-operation: a Transnationmentioning
confidence: 98%
“…The rise in the material living standards of mining workers boosted consumption demand, and spilled over to other local economic sectors (breweries, food processing and cement industries, as well as electric power plants). 27 Political and trade union freedom was gradually allowed and the segregation policy was abandoned (Buelens and Marysse 2009).…”
Section: Towards Stabilization At Umhkmentioning
confidence: 99%
“…The Japanese joined the colonialism movement but engaged in finding ways to gain from the comparative advantages of the country they entered into (Hsiao and Hsiao, n.d.).What is being noticed is that the goal of colonialism is a factor that impacts the colony. We have seen that some countries make changes in industry that positively affect the colony (Hsiao and Hsiao, n.d.) while some engage in extractive activity that puts the colony's economy at risk (Buelens and Marysse, 2009).…”
Section: Economic Development and Rule Of Law Colonizationmentioning
confidence: 99%